Water-based immobilized Ag-doped TiO₂ photocatalyst for photocatalytic degradation of RR4 dye / Nureel Imanina Abdul Ghani ... [et al.] - Abdul Ghani, Nureel Imanina; Rosli, Muhammad Afiq; Hamzah, Siti Raihan; Natar, Nadiah Sabihah; Nazeri, Nur Syazana; Ab Aziz, Syahirul Ikhwan; Mohamad, Sarina; Wan Ismail, Wan Izhan Nawawi (UiTM Press, 2022)
This study used water-based preparation of immobilised Ag-TiO2 using the DSAT technique to avoid solvent interference of Ag-TiO2 photocatalytic performance. The preparation of Ag-TiO2 was conducted via the photodeposition method with silver nitrate (AgNO3) as Ag precursor at various ratios of Ag dopant to TiO2. The immobilisation of Ag-TiO2 was prepared via water-based immobilisation using the DSAT method, and XRD and FESEM-EDX characterised the obtained photocatalyst. The photocatalytic performance of Ag-TiO2 was measured by photocatalytic degradation of Reactive Red 4 (RR4) dye. The optimum photocatalytic performance of suspension mode Ag-TiO2 was obtained at 3 % of Ag-TiO2. Sample 3 % Ag-TiO2 was applied under immobilisation mode with complete degradation of 30 mg/L RR4 dye achieved within 60 min under 55 W fluorescent lamp irradiation. It is 36 % faster compared to immobilised, unmodified TiO2. The acquired results from FESEM-EDX indicated the presence of 0.6 % Ag on the Ag-TiO2 photocatalyst sample. The photodegradation rate of immobilized 3 % Ag-TiO2 sample under different solvents has shown the different values among all where it was 0.096 > 0.037 > 0.029 > 0.029 > 0.025 min-1 for water-base, ethanol, methanol, dichloromethane and acetone respectively. Thus, the solvents can influence the photocatalytic performance of the immobilised 3 % Ag-TiO2 photocatalyst by molecular interference between Ag-doped in TiO2. The water-based immobilised 3 % Ag-TiO2 sample also has a sustainable performance where the photocatalytic activities are comparable to 10 cycles.